Functional connectivity of the prefrontal cortex in Huntington's disease. Issue 2 (6th October 2006) - Thiruvady, D R; Georgiou-Karistianis, N; Egan, G F; Ray, S; Sritharan, A; Farrow, M; Churchyard, A; Chua, P; Bradshaw, J L; Brawn, T-L; Cunnington, R
Abstract : Background: Huntington's disease is a progressive neurodegenerative disorder that results in deterioration and atrophy of various brain regions. Aim: To assess the functional connectivity between prefrontal brain regions in patients with Huntington's disease, compared with normal controls, using functional magnetic resonance imaging. Patients and methods: 20 patients with Huntington's disease and 17 matched controls performed a Simon task that is known to activate lateral prefrontal and anterior cingulate cortical regions. The functional connectivity was hypothesised to be impaired in patients with Huntington's disease between prefrontal regions of interest, selected from both hemispheres, in the anterior cingulate and dorsal lateral prefrontal cortex. Results: Controls showed a dynamic increase in interhemispheric functional connectivity during task performance, compared with the baseline state; patients with Huntington's disease, however, showed no such increase in prefrontal connectivity. Overall, patients with Huntington's disease showed significantly impaired functional connectivity between anterior cingulate and lateral prefrontal regions in both hemispheres compared with controls. Furthermore, poor task performance was predicted by reduced connectivity in patients with Huntington's disease between the left anterior cingulate and prefrontal regions. Conclusions: This finding represents a loss of synchrony in activity between prefrontal regions in patients with Huntington's disease when engaged in the task, which predicted poor task performance. Results show that functional interactions between critical prefrontal regions, necessary for cognitive performance, are compromised in Huntington's disease. It is speculated whether significantly greater levels of activation in patients with Huntington's disease (compared with controls) observed in several brain regions partially compensate for the otherwise compromised interactions between cortical regions.